Assessment of impacts of tourism on poverty alleviation in Vietnam: A panel data approach - Pham Thi Thuy Hang; Nguyen Minh Thu; Nguyen Thi Minh Anh (My University, 2023)
Assessment of impacts of tourism on poverty alleviation in Vietnam: A panel data approach
Keywords: Tourism